Damage caused by cattle to Eucalyptus benthamii trees in pruned and unpruned silvopastoral systems - Triches, Gilmar Paulinho; Moraes, Anibal de; Porfírio-da-Silva, Vanderley; Lang, Claudete Reisdorfer; Lustosa, Sebastião Brasil Campos; Bonatto, Rafael Araújo (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the effect of tree pruning on the incidence and intensity of the damages caused by cattle to 26-month-old Eucalyptus benthamii, in a silvopastoral system, in the municipality of Pinhais, in the state Paraná, Brazil. The experiment was performed in a randomized complete block design, with two treatments – livestock and forest with pruned eucalyptus (WP), and livestock and forest with unpruned eucalyptus (UP) – and three replicates, characterizing six types of damages and five damage intensities. There were significant differences between the WP and UP treatments for the different types of damages. Cattle entry in the silvopastoral system at 26 months after the planting of eucalyptus causes low-intensity damages to the trees, in the treatment with pruning, and medium-intensity damages to the trees in the treatment without pruning. Damages of stronger intensities were detected in the UP treatment, in which class-two damages (d2 = average damage) were verified in approximately 91% of the trees. The silvicultural practice of pruning E. benthamii trees does not affect the diameter at breast height or the total height of trees. Pruning can be recommended, as it does not affect tree development; moreover, this practice enables the production of knot-free, better-quality wood.